The contribution of project-based learning to improve basic literacy at junior high school - Elisabet Janul; Dadang Sunendar (Himpunan Pengembang Kurikulum Indonesia, 2024)
Collaboration is one of the skills needed in the 21st century. Santa Angela Middle School responded to this demand by designing a collaborative project between subjects. This research aims to analyze the contribution of collaboration projects between subjects to developing students' literacy skills. Based on the results of observations and interviews, the collaborative learning model has a major contribution to the development and mastery of students' basic literacy. This is possible because students can learn several subjects in the collaboration model between students in one project. This approach pattern allows students to be trained to analyze, understand, and find solutions to every problem encountered in everyday life. Collaborative projects provide opportunities for students to collaborate with peers. This research uses a descriptive method with a qualitative approach. This research shows that collaborative projects between subjects contribute to students' literacy skills. Through collaborative learning activities between subjects of various types, students' basic literacy skills experience significant changes and improvements. This happens because, in the collaborative learning process between subjects, students must have more reading comprehension by looking for important information related to the discussed topic. Abstrak Kolaborasi merupakan salah satu keterampilan yang dibutuhkan diabad 21. Sekolah Santa Angela menjawab kebutuhan ini dengan mendesain proyek kolaborasi antar mata pelajaran. Penelitian ini bertujuan menganalisis kontribusi proyek kolaborasi antar mata pelajaran terhadap pengembangan kemampuan literasi peserta didik. Berdasarkan hasil observasi dan wawancara model pembelajaran kolaborasi memiliki kontribusi yang besar terhadap perkembangan dan penguasaan literasi dasar peserta didik. Hal ini dimungkinkan karena dalam model kolaborasi antar mata pelajaran, peserta didik dapat belajar beberapa mata pelajaran dalam satu proyek. Pola pendekatan ini memungkinkan peserta didik dilatih untuk menganalisis, memahami dan menemukan solusi dari setiap persoalan ditemukan dalam kehidupan sehari-hari. Proyek kolaborasi memberi kesempatan kepada peserta didik untuk menjalin kerja sama dengan teman sebaya. Penelitian ini menggunakan metode deskriptif dengan pendekatan kualitatif. Hasil dari penelitian ini menunjukkan bahwa proyek kolaborasi antar mata pelajaran memberi kontribusi terhadap kemampuan literasi peserta didik. Melalui kegiatan pembelajaran kolaborasi antara mata pelajaran berbagai jenis kemampuan literasi dasar peserta didik mengalami perubahan dan peningkatan yang cukup signifikan. Hal ini terjadi karena dalam proses pembelajaran kolaborasi antar mata pelajaran peserta didik dituntut untuk lebih banyak membaca pemahaman dengan mencari informasi-informasi penting yang berkaitan dengan topik yang dibahas. Kata Kunci: literasi; pembelajaran berbasis proyek; pembelajaran kolaborasi